High Precision Measurement and Evaluation of the Fine Mould Surface Structures - Durakbasa, M. N.; Osanna, P. H.; Yurci, M. E.; Nomak-Akdogan, A. (TRANS TECH PUBLICATIONS LTD, 2008)
Surface structure is a suitability state that must be pursued closely workpiece components which work under severe conditions. It is a fact that high-precision forming component's surface roughness affects the product's nature that is being formed. In this scientific perspective, measurement and evaluation of the surface roughness and surface texture diversities during manufacturing and the effects of these diversities on material performance and product suitability has a significant importance. The first objective of the present project is to define surface modification treatments and the surface characteristics which will improve the performance of forming dies particularly for the glass industry. In this experimental work the results of the high-precision measurements on the mould surfaces discussed in detail and the surface characteristics of DIN 1.2080 steel and the surface boronized one of the same material are compared and the effects of surface roughness and surface texture are investigated in a wide perspective.
Keywords: Precision; Surface Roughness Measurement; Tactile Measurement; Mould Surface; Surface Texture; AFM; ROUGHNESS; TEXTURE; Instruments & Instrumentation; Materials Science